Comparative evaluation of healing response between colo-colic invagination anastomosis and single-layer running suture. Experimental study in dogs - Nogueira,Miguel Augusto Arcoverde (2016)
Abstract Objective Evaluate healing response of colo-colic anastomosis by invagination vs. single-layer suture. Methods Sixty dogs were randomly distributed in two groups and anastomosed with single-layer suture (G-I, control) or by invagination and cardinal sutures (G-II, study). In the end, the animals were euthanized (10 from each group on POD7 and 20 on POD21) and the anastomosed segment was retrieved for histology and immunohistochemistry. Parameters included body weight, adhesions, edema, vasoproliferation, type I and III collagen, myeloperoxidase and nitric oxide. Findings were analyzed with Student's t test and the Mann–Whitney test. Results No animal died prior to euthanasia. The groups were similar with regard to all parameters: median weight 10.86 kg (G-I) and 9.98 kg (G-II) on POD7 (p = 0.41) and 11.86 kg (G-I) and 11.55 kg (G-II) on POD21 (p = 0.71); abdominal adhesions (p = 0.7383 POD7; p = 0.5685 POD21), level of edema (p = 0.3006 POD7; p = 0.7990 POD21), vasoproliferation (p = 0.1191 POD7; p = 0.0758 POD21), type I collagen (p = 0.4591 POD7; p = 0.3357 POD21), type III collagen (p = 0.2166 POD7; p = 0.2712 POD21), nitric oxide (p = 0.3980 POD7; p = 0.4796 POD21) and myeloperoxidase (p = 0.580 POD7; p = 0.755 POD21). Conclusion No significant difference in healing response was observed between the two anastomosis techniques (single-layer suture and invagination).